PENGARUH KUALITAS PELAYANAN TERHADAP KEPUASAN DAN LOYALITAS PELANGGAN RESTORAN CEPAT SAJI - I Putu Utama; I Gusti Ngurah Agung Suprastayasa; I Nyoman Wiratnaya (JURNAL KEPARIWISATAAN, 2011)
This research proposes to confirm the effects of service quality to customert s satisfaction and loyalty in fast food restaurants. The data were collected by applying judmental sampling method, which was applied to 200 customers at outlets of Kentucky Fried Chicken and Mac Donalds in Denpasar and Badung. The variables in this study are service quality as an exogenous variable, customers satisfaction as an interviening variable, and customers loyalty as an endog-enous variable. The responden s perception is indicated in Likert scale of 5, in which I is strongly disagree and 5 is strongly agree with the statements. The data were then analyzed using Structural Equation Modelling (SEM). The questioner consisting of 40 questions were tried out for its validity using Alpha Pearson Correlation and reliability using Cronbach s alpha formulas. Then, the statistical analysis of Structural Equation Modelling showed that direct effect of service quality to customers satisfaction was sign.ificant (85.9%), direct effect of customers satisfaction to customers loyalty was significant (91.5%), direct effect of service quality to customers satisfaction was insign.ificant, and indirect effect of service quality to customers loyalty through customers satisfaction was significant (78.6%).